(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A survey that was conducted by British Social Media Company found that of a total of 268.2 million people in Indonesia, 150 million of them have used social media. Social media allows consumers to access thousands of pieces of information every day through the internet. Consumers can discuss brands with one another quickly and easily online. Consumer opinions about products and services online are now increasing and, in turn, affect opinion in an offline state. Internet users can provide reviews and ratings for all types of products, brands, and services. These reviews can be positive or negative statements; product reviews and services in the form of positive statements encourage consumer purchasing decisions. This study seeks to explore and investigate whether a review of the quality of bank services through social media will encourage the selection of banks by depositors. This research design is qualitative research design. The population in this study consisted of millennials residing in the city of Bandung, amounting to 912 thousand inhabitants. Samples to be taken are as many as 250 people. The research data was obtained through a questionnaire. The results showed that almost all the reviews that appear on social media will be able to encourage depositors to choose a bank. Reviews on bank performance and easy and fast transaction services can provide comfort to all customers. In addition, reviews of high performance from employees, such as friendliness, ability to provide fast responses to customers, being skilled, highly motivated, and having high initiative, encourage the selection of banks by depositors.